Integrating a Teaching Concept for the Use of Virtual Reality in University Teaching - Henrich, Adrian; Schultze, Tobias; Weisbecker, Anette; Riedel, Oliver (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
As many of the common mistakes made by engineering students are based on weak spatial imagination, the use of virtual reality could help to enhance those skills in undergraduate teaching. As part of a university lecture in product development that covers methods of product development and technical design, the use of virtual reality was integrated into an engineering exercise. Supplementing the usual technical tools like CAD, half of the 14 student groups were allowed to use a dedicated VR-application to review their machine designs in virtual reality. While the objective performance of those groups was not better in comparison to the "non-VR" groups, most of the student groups were able to identify design issues or mistakes through the use of VR, which they couldn't find using only CAD. According to interviews, 69.7% of the VR-users reported that they were only able to experience and realize "the true spatial dimensions" through the use of VR.